2013
DOI: 10.2319/111312-869.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone morphometric changes on orthodontic tooth movement in an osteoporotic animal model

Abstract: Objective: To elucidate the effect of bone morphometric changes on orthodontic tooth movement (OTM) in zoledronic acid-treated ovariectomized rats. Materials and Methods: Twenty-one 10-week-old female Wistar rats were divided into ovariectomy (OVX), OVX with zoledronic acid administration (OVX + ZOL), and sham operation (control) groups. Two weeks after OVX, ZOL administration was initiated. Twelve weeks after OVX, a nickel-titanium closed-coil spring of 25-g force was applied mesially to the maxillary left fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
0
15
2
2
Order By: Relevance
“…In contrast, a lower rate of tooth displacement and alveolar bone turnover in T1D rats without treatment was reported. These studies do not agree with the substantial evidence linking T1D to osteopenia, osteoporosis, and related cellular and molecular mechanisms, or with studies showing a higher rate of tooth displacement and root resorption in T1D individuals . Therefore, our results suggest that T1D induces fragile bone that cannot support light forces that in turn become too excessive for the periodontal structures leading to breakdown and a different OTM pattern.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, a lower rate of tooth displacement and alveolar bone turnover in T1D rats without treatment was reported. These studies do not agree with the substantial evidence linking T1D to osteopenia, osteoporosis, and related cellular and molecular mechanisms, or with studies showing a higher rate of tooth displacement and root resorption in T1D individuals . Therefore, our results suggest that T1D induces fragile bone that cannot support light forces that in turn become too excessive for the periodontal structures leading to breakdown and a different OTM pattern.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies do not agree with the substantial evidence linking T1D to osteopenia, 3 osteoporosis, 12 and related cellular and molecular mechanisms, 3,34 or with studies showing a higher rate of tooth displacement and root resorption in T1D individuals. 46,47 Therefore, our results suggest that T1D induces fragile bone that cannot support light forces that in turn become too excessive for the periodontal structures leading to breakdown and a different OTM pattern. Generally, the impaired bone metabolism in T1D children and adolescents reduces peak bone accrual, predisposing the adult to osteopenia and osteoporosis.…”
Section: Discussionmentioning
confidence: 78%
“…The device used to induce OTM consisted of a nickel-titanium closed coil spring (G&H (r) Wire - Franklin, Indiana, USA) attached to maxillary right first molar and central incisors of all animals, which produced a 25-cN reciprocal force 14. Measurement of the force produced by the coil spring was standardized by means of a calibrated dynamometer (Haag-Streit AG, Switzerland Koeniz, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Various factors have been reported to influence OTM. 6,7 Hashimoto et al 8 reported a negative correlation between OTM and bone morphometric measurements, such as trabecular bone structure in ovariectomized rats. It was also reported that tooth movement increased and the optical density of bone decreased on administration of fluoxetine to the rats.…”
Section: Introductionmentioning
confidence: 99%